2012
DOI: 10.1080/13623699.2012.658627
|View full text |Cite
|
Sign up to set email alerts
|

Towards the responsible conduct of scientific research: is ethics education enough?

Abstract: Much of the discourse on 'beyond the laboratory door' biosecurity to date has focused on the need to raise awareness among the scientific community of the risks posed by the rapid advancement of biotechnology in recent decades. While education is undoubtedly important, a growing body of evidence suggests that ethics education does not necessarily translate into ethical behaviour. This trend has already been reported in clinical settings, where research has highlighted doctors' own reports of ethically dubious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…There are ethical implications of conducting research entirely online. IT is advancing faster than ethical review panels can address and there is a need for greater ethical consideration of conducting research online and how we share data between IT systems and within organizations . Government attempts to legislate – the Health Insurance and Portability Act in the USA, and the Data Protection Act in the UK, have had little impact on alleviating public scepticism .…”
Section: Resultsmentioning
confidence: 99%
“…There are ethical implications of conducting research entirely online. IT is advancing faster than ethical review panels can address and there is a need for greater ethical consideration of conducting research online and how we share data between IT systems and within organizations . Government attempts to legislate – the Health Insurance and Portability Act in the USA, and the Data Protection Act in the UK, have had little impact on alleviating public scepticism .…”
Section: Resultsmentioning
confidence: 99%
“…High-school bioethics and biosafety education has been also suggested (Evans, 2014), as well as continued professional development to maintain engagement with biosecurity issues (Novossiolova & Sture, 2012) Revill et al (2012) concluded, on the basis of different dual-use educational experiences, "that there is no 'one size fits all' approach to the implementation of dual-use education. Rather, initiatives must be tailored to suit the teaching traditions, geographical and historical context in which they are being delivered.…”
Section: Education and Raising Of Awareness Of Dual-use Risksmentioning
confidence: 99%
“…The National Institutes of Health [28] require that "RCR training" spans the scientists' career and Novossiolova and Sture (2012) [20] (pp. 80-81) recommended "continuing professional development" in ethics for scientists, and they call for research on how this might be achieved and assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The National Academy of Engineering [19] (p. 36) declares this to be a flawed model for ethics education; and Novossiolova and Sture (2012) [20] reviewed the literature around ethics education and describe how this type of educational experience-even if successfully delivered-can fail to be brought to bear in practice. This failure may arise from the learning itself (e.g., [21]), or from perceived failures of the applicability of the ethics instruction to real world contexts and situations.…”
mentioning
confidence: 99%